The Influence of the Service Marketing Mix on the Purchase Decision of Feb Uki Services With Social Media as a Variable Moderation on Promotions - Napoleon Sinaga; Iwan Kresna Setiadi; Maria Assumpta Wikantari; Fenny B.N.L Tobing (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to investigate the influence of the service marketing mix on purchase decisions at the Faculty of Economics and Business at UKI, with social media as a moderation variable in promotion. Data were collected through surveys of students selecting programs at the faculty. Hypothesis testing results indicate that product, price, place, physical evidence, and administrative processes do not significantly influence purchase decisions. However, promotion and personal factors significantly affect purchase decisions, with promotion showing a significant positive path coefficient. Furthermore, social media, as a moderation variable in promotion, also significantly influences purchase decisions. The implications of these findings underscore the need for marketing strategies focused on promotion through social media to enhance attractiveness and positive influence on prospective students at FEB UKI. This study contributes to understanding the dynamics of service marketing in higher education contexts, utilizing social media as a primary tool to achieve marketing objectives.